2006
DOI: 10.1002/pssa.200622415
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube via interconnect technologies: size‐classified catalyst nanoparticles and low‐resistance ohmic contact formation

Abstract: We propose a new approach to fabricating carbon nanotube (CNT) via interconnects for future LSIs, which uses preformed catalyst nanoparticles to grow the CNTs. A newly designed impactor provided size‐classified catalyst particles. For the new approach, we employ a TiN contact layer which is more resistant to oxidation and enables us to form a lower resistance ohmic contact between CNTs and wiring layers. The resultant CNT–via resistance was 0.59 Ω for 2‐µm vias, which is the smallest ever reported. We also stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
60
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 6 publications
0
60
1
Order By: Relevance
“…The present status of work on Vias is that Kreupl et al [5,6] of Infineon did the early work on showing nanotube growth out of holes for Vias, but now the present leader is Awano et al [9][10][11] of Fujitsu. They have achieved a MWNT density of over 10 11 cm -2 , and are also working on the contacting problem.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The present status of work on Vias is that Kreupl et al [5,6] of Infineon did the early work on showing nanotube growth out of holes for Vias, but now the present leader is Awano et al [9][10][11] of Fujitsu. They have achieved a MWNT density of over 10 11 cm -2 , and are also working on the contacting problem.…”
Section: Introductionmentioning
confidence: 94%
“…1) will soon exceed the maximum the maximum allowed by Cu of ~6. 10 6 A.cm -2 before it fails due to electromigration. This is expected to occur at the 22 nm node (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Nowadays, electrical mobility analysis is a worldwide used technique to control particle size in gas phase synthesis of nanomaterials under atmospheric pressure conditions in the laboratory (Maisels et al 2002a;Nasibulin et al 2005;Awano et al 2006;Kim and Zachariah 2007). Basically, the aerosol passes first through a device where the particles acquire a charge distribution (aerosol charger) and then enters a Differential Mobility Analyzer (DMA) where particles are classified based on the electrical mobility, which is a function of the particle size, charge, and shape.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of the bundle decreases with diameter, which is to be expected as more CNT can conduct in parallel for larger bundles. The good contact between the CNT and the metals is attributed to the use of Ti 19 , and TiN which is more resilient against oxidation 21 . Besides, we found that due to the lack of any dielectric covering steps of the CNT after growth (using for instance spin-on glass), something which is often used in the literature in combination with chemical mechanical polishing (CMP) 22,23 , the contact resistance to the CNT is low due to embedding of the CNT tips in the top metal 24 .…”
mentioning
confidence: 99%